Comparative Assessment of Ecological Plasticity of the Steppe Marmot Between Ukrainian and Kazakhstan Populations: Challenges of the Man-Induced Environmental Changes - Ronkin, Vladimir; Tokarsky, Victor; Polchaninova, Nina; Atemasov, Andrey; Koshkina, Alyona; Savchenko, Galina (Frontiers in Ecology and Evolution, 2020)
The steppe marmot inhabits a wide range of open dry grasslands. Throughout this vast area, the marmot’ habitat has undergone major changes due to human activities. Long-term ecological monitoring has been conducted in the European steppe marmot (Marmota bobak bobak) settlements in Northeastern Ukraine in 2001–2019. These data are compared with ecological conditions of Marmota bobak schaganensis settlements in Kazakhstan observed by us in 2017.The goals of our investigation were: (1) to estimate the M. bobak ecological plasticity based on the range of vegetation characteristics of its habitats and settlement structure; (2) to juxtapose population density of the European subspecies with the food base of its habitats; (3) to evaluate population response of M. b. bobak to the abandonment of cattle grazing; (4) to ascertain new ecological adaptations (if any) to habitat changes; (5) to reveal the difference in “plant-herbivore” interactions in the ecosystems of Northeastern Ukraine and Northern Kazakhstan. We found a great difference in ecological features of M. b. bobak and M. b. schaganensis in populations locating at extreme points of the species ecological niche. The European steppe marmot was and continues to be a secondary pasture user. The Kazakhstan subspecies can be both secondary and primary user of the Asian dry steppes. According to our results, the habitats of the European steppe marmot worsened dramatically in compare with the Kazakhstan subspecies. Diverse habitats with a range of vegetation parameters, as well as the differences between the settlement structures of M. b. bobak and M. b. schaganensis evidence a high ecological plasticity of the steppe marmot at the species level. At the same time, we don’t find new ecological adaptations that would ensure the survival of M. b. bobak settlements in modern conditions of total abandonment of cattle grazing.